2015
DOI: 10.1128/aac.00073-15
|View full text |Cite
|
Sign up to set email alerts
|

MIV-150/Zinc Acetate Gel Inhibits Cell-Associated Simian-Human Immunodeficiency Virus Reverse Transcriptase Infection in a Macaque Vaginal Explant Model

Abstract: The transmission of both cell-free and cell-associated immunodeficiency viruses has been demonstrated directly in multiple animal species and possibly occurs in humans, as suggested by genotyping of the infecting human immunodeficiency virus (HIV) in acutely infected women and in semen from their partners. Therefore, a microbicide may need to block both mechanisms of HIV transmission to achieve maximum efficacy. To date, most of the preclinical evaluation of candidate microbicides has been performed using cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Primers for SIV were 5′-GGTTGCACCCCCTATGACAT-3′ (SIV667 gag Fwd) and 5′-TGCATAGCCGCTTGATGGT-3′ (SIV731 gag Rev). Results were analyzed by the standard curve method, using SIV mac1A11 DNA obtained from Dr. Paul Luciw through the NIH AIDS Reagent Program, Division of AIDS, NIAID, NIH 52 as the standard ( 37,65 . Primers for HSV-2 pol were 5′-GCTCGAGTGCGAAAAAACGTTC-3′ (HSV-2 pol Fwd) and 5′-TGCGGTTGATAAACGCGCAGT-3′ (HSV-2 pol Rev) 13,53 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers for SIV were 5′-GGTTGCACCCCCTATGACAT-3′ (SIV667 gag Fwd) and 5′-TGCATAGCCGCTTGATGGT-3′ (SIV731 gag Rev). Results were analyzed by the standard curve method, using SIV mac1A11 DNA obtained from Dr. Paul Luciw through the NIH AIDS Reagent Program, Division of AIDS, NIAID, NIH 52 as the standard ( 37,65 . Primers for HSV-2 pol were 5′-GCTCGAGTGCGAAAAAACGTTC-3′ (HSV-2 pol Fwd) and 5′-TGCGGTTGATAAACGCGCAGT-3′ (HSV-2 pol Rev) 13,53 .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of gel activity against SHIV-RT and HSV-2 was performed as described in 36,37,39,40,54 using a log-normal generalized linear mixed model with SOFT or CUM as the response and gel treatment as the predictor. For the experiments using rectal biopsies, a random intercept for each animal was included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, gels incorporating macromolecules such as proteins, multipurpose technology (MPT) products that combine HIV and other STI prevention, and dual compartment products, represent some of the most recent activities within this class. A combination microbicide gel containing MIV-150 and zinc acetate formulated in a carrageenan gel showed efficacy against HIV-1, HSV-2, and HPV in macaques after vaginal and rectal challenges [91]. A phase-1 study showed that this product is safe, and the cervicovaginal lavages (CVLs) show in vitro activity against HIV-1 and HPV [16].…”
Section: On-demand Vaginal Rectal and Dual Compartment Dosage Formsmentioning
confidence: 99%
“…CG is the most potent inhibitor of HPV known, 26 potentiates the anti-HSV-2 activity of ZA, 27,28 and has been found safe for vaginal use in multiple studies. 2934 PC-1005 is active in vivo against vaginal or rectal challenge with HIV, simian-human immunodeficiency virus-reverse transcriptase, HSV-2, and HPV 24,35,36 ; ex vivo against simian-human immunodeficiency virus-reverse transcriptase in explants 37,38 and remains active in the presence of semen. 27,28 …”
Section: Introductionmentioning
confidence: 99%